2020
DOI: 10.21733/ibad.798006
|View full text |Cite
|
Sign up to set email alerts
|

Müzik Öğretmenliği Lisans Öğrencilerinin Çalgı Sınavındaki Performans Kaygı Düzeylerinin Çeşitli Değişkenlere Göre İncelenmesi

Abstract: This article was checked by iThenticate. Similarity Index 23% Bu makalede araştırma ve yayın etiğine uyulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
1
0
6
Order By: Relevance
“…When the studies on this variable were examined, it was seen that the self-efficacy perception levels of the students regarding stage management differed significantly according to the individual instrument types (Birdal, 2021). In another study, it was concluded that there was a significant difference between the trait anxiety level of music teaching students in terms of instruments, but there was no significant difference between the anxiety level of statefulness (anxiety that occurs at a certain moment and under a certain condition) (Umuzdaş & Tök, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…When the studies on this variable were examined, it was seen that the self-efficacy perception levels of the students regarding stage management differed significantly according to the individual instrument types (Birdal, 2021). In another study, it was concluded that there was a significant difference between the trait anxiety level of music teaching students in terms of instruments, but there was no significant difference between the anxiety level of statefulness (anxiety that occurs at a certain moment and under a certain condition) (Umuzdaş & Tök, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Aykanat'ın (2018) okul öncesi öğretmenleri ile yapmış olduğu çalışmanın sonucunda öğretmenlerin sanat eğitimine yönelik olumlu tutum sergiledikleri bu araştırmanın sonucu ile örtüşmektedir. Elde edilen bulgular yapılmış olan diğer araştırmalarla (Afacan, 2016;Umuzdaş & Kızıklı, 2018;Koca, 2013;Magsamen & Battro, 2011;Szecsi, 2008;Umuzdaş & Umuzdaş, 2015;) benzerlik göstermektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Buradan anlaşılacağı üzere; araştırmada elde edilen nitel ve nicel veri sonuçlarının birbiriyle tutarlı ve destekleyici olduğu görülmektedir. Öte yandan ölçekten elde edilen bu sonuç, yapılan diğer çalışmalarla da benzerlik göstermiştir (Kalın, 2021;Umuzdaş & Umuzdaş, 2015).…”
Section: Müzik Dersi Rahatlatır Huzur Verir İyileştirir Ve Dinlendirirunclassified
“…Bunun sonucu olarak da istenilen davranış şekillerinin kazandırılması ve olumlu tutumların geliştirilmesi için gerekli koşulların oluşturulması ve önlemleri almamızı sağlaması yönüyle de oldukça önemli görülmektedir (İnceoğlu, 2010). Tutumlar ile ilgili yapılan çalışmalar incelendiğinde, tutum çalışmalarının çoğunlukla (Ayhan, 2019;Kocaarslan, 2009;Kocabaş, 1997;Nacakçı, 2006;Otacıoğlu, 2007;Öztopalan, 2007;Umuzdaş & Umuzdaş, 2015;Yıldız, 2021) ilköğretim düzeyinde yapıldığı görülmektedir. Ayrıca sınırlı sayıda (Bayram-Koç, 2019;Gergin, 2010;Koca, 2013;Selçuk-Otlak, 2019;Özmenteş & Özmenteş, 2009;Yazıcı, 2018) ortaöğretim ve lisans düzeyinde yapılan çalışmaların olduğu da bilinmektedir.…”
Section: Introductionunclassified